Revealing the atomic-scale evolution of sessile disconnections on twin boundaries during deformation. (December 2022) - Kou, Zongde; Huang, Rong; Yang, Yanqing; Feng, Tao; Tang, Song; Lan, Si; Yang, Lixia
Abstract: Sessile disconnections on twin boundaries (TBs) are special interfacial defects which can not glide conservatively along TBs, playing an important role in plastic deformation of twin-containing metals. However, the detailed aspects of the evolution of sessile disconnections on TBs under stress are not yet fully understood, while the direct atomic-scale experimental evidence remains rare. By integrating the in situ transmission electron microscope tensile test, multichromatic complex analysis method and molecular dynamics simulation, we studied the evolution of sessile disconnections on TBs. Dislocation reaction analysis shows that sessile disconnections can serve as effective nucleation sites of twinning dislocations (TDs) which lead to the migration of TBs. Moreover, twin-twin intersections can also act as sinks for gliding lattice dislocations by transforming lattice dislocations into TDs along different twining systems. This work enriches the knowledge of the atomic-scale deformation mechanism of twin-containing metals. Graphical abstract: Image, graphical abstract